E-view: low vision reader assistant - Zainol, Omar; Hamzah, Noor Azlina; Md Hasan, Hasrizal; Mohd, Hamidah; Baharom, Mat Asri; Mohd Sidik, Shazmie Huzni; Zainol, Mohd Amin (Universiti Teknologi Mara, Kedah, 2022)
E-view (enhanced view) was developed to improve the Perpustakaan Sultan Badlishah (PSB) services as an initiative to provide the visually impaired to improve their visual ability in making references through reading. The PSB is continuously committed to realizing OKU participation: no one is left behind in the development of agenda 2030. E-view targets users with retinitis pigmentosa and low vision at levels b1 and b2, which can make the most of e-view with a wide range of colour contrast options through integration with text recognition applications. Through this innovation, the library is ready to provide the best service to each group of disabled users through an improvement that can be explored and applied to the e-view tool. By using basic tools that are readily available, e-view can be built easily and quickly without incurring high costs as compared to the tools available in the market. Usually, it needs to be imported from abroad and is very expensive. The application is open source, built into the operation of the window, and does not require additional costs. This has a significant impact in supporting the savings practiced by UiTM generally without compromising the quality of service to consumers. With the advent of e-view, users with low vision disabilities can no longer make printed material as references. Limited visibility is no longer a hindrance to them using the reference facilities in the library. E-view also allows users to screenshot reference materials in the form of high contrast that corresponds to the low vision level faced by the user so that it can be stored on a mobile phone or laptop for future reference without having to be printed with high contrast colours. E-view components are easily acquired, making it an ideal tool to place in the library as it does not use ample space due to its small size and portability. The project is fully supported by the director of Unit Perkhidmatan OKU (UPO), UiTM Shah Alam, because of the impact and benefits for the disabled who need special equipment to help them continue their studies in UiTM.